Scimitar sign with normal pulmonary venous drainage and anomalous inferior vena cava. Issue 8 (August 1988) - Herer, B; Jaubert, F; Delaisements, C; Huchon, G; Chretien, J
Abstract : A case of the scimitar sign due to an anomaly of the right sided pulmonary vein with normal drainage into the left atrium was associated with an azygos continuation of the inferior vena cava. Digital subtraction angiography allows the identification of these rare congenital vascular malformations.